2021
DOI: 10.3390/ani11072081
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory, Sedative and Antinociceptive Effects of a Medetomidine Constant Rate Infusion with Morphine, Ketamine or Both

Abstract: Standing surgery under sedation reduces anesthetic-related mortality in horses. Medetomidine, alone and combined with morphine in a constant rate infusion (CRI), has been described for standing surgery but their cardiorespiratory, sedative and antinociceptive effects have never been compared. The addition of ketamine could improve analgesia in these procedures with minimal cardiorespiratory consequences. The objectives were to compare the cardiorespiratory effects, quality of sedation, antinociception and atax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…During long-term standing procedures for horses, alpha-2 agonists are commonly used as a single bolus followed by a CRI [ 4 , 5 , 6 ]. Several studies have shown that combining alpha-2 agonists with opioids increases the level of sedation and analgesia, improves chemical restraint, and decreases the response of the animal to environmental stimulation [ 4 , 7 , 8 , 9 ]. Two studies have demonstrated that the combination of methadone and the infusion rate of detomidine improves sedation and analgesia in horses [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During long-term standing procedures for horses, alpha-2 agonists are commonly used as a single bolus followed by a CRI [ 4 , 5 , 6 ]. Several studies have shown that combining alpha-2 agonists with opioids increases the level of sedation and analgesia, improves chemical restraint, and decreases the response of the animal to environmental stimulation [ 4 , 7 , 8 , 9 ]. Two studies have demonstrated that the combination of methadone and the infusion rate of detomidine improves sedation and analgesia in horses [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antinociceptive, cardiorespiratory, and sedative effects of a medetomidine constant rate infusion with morphine, ketamine, or both were recently investigated in a horse [ 9 ], demonstrating that a CRI administration of 5 μg/kg of medetomidine combined with 50 μg/kg of morphine is safe and provides a proper degree of antinociception and sedation, in the absence of clinically relevant changes in cardiorespiratory variables. Similar results were obtained in this study, where the range of HR and RR remained constant in both groups, with the exception of one horse in Group D that presented tachycardia 5 min after the end of morphine inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedation protocols vary greatly in clinical practice, and objective methods for assessing sedation depth and quality are critical for studies seeking to identify optimal protocols for potentially painful procedures. Published methods of sedation assessment in horses often rely on the height of the head above the ground (HHAG) and observation of behaviors such as ataxia, or observation of behaviors such as ataxia; and chewing and head movement 20‐23 . More recently, a facial scale has been described for evaluating sedation in horses 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Published methods of sedation assessment in horses often rely on the height of the head above the ground (HHAG) and observation of behaviors such as ataxia, or observation of behaviors such as ataxia; and chewing and head movement. [20][21][22][23] More recently, a facial scale has been described for evaluating sedation in horses. 24 While well-suited for assessing sedation depth in standing, undisturbed horses, these methods are not easily applied to sedated horses undergoing a potentially painful stimulus.…”
Section: Discussionmentioning
confidence: 99%